Connecting to the Sea: A Place-Based Study of the Potential of Digital Engagement to Foster Marine Citizenship - Katharine Willis; Ashita Gupta (Urban Planning)
The Sustainable Development Goals for creating sustainable, resilient cities and addressing human impacts upon coastal waters and marine environments create a mandate for coastal cities to empower local communities to value city seascapes. One key way to achieve this is through more inclusive pathways to connect to the sea using participatory methods. This research used a participatory co-design approach in Plymouth—the UK’s first national marine park—to explore the potential for place-based digital engagement to connect people with the sea, especially for deprived neighbourhoods. We sought to answer the research question of whether place-based digital technologies can engage communities with marine spaces and make coastal areas more accessible. Using the collaborative community-led concept of a city marine park, we explored the requirements for digital technologies needed to create marine citizenship and address the challenge of building coastal resilience. We describe a participatory action research study that took place in an urban coastal community, run in collaboration with a local organisation, the Rockpool Project, over a period of six months. Through a baseline survey, we identified some of the barriers to accessing the sea and ways in which the sea was perceived as a space in the city. We also ran a series of co-design workshops using creative prototyping with local families to help define the requirements for a digital toolkit that could enable them to access the sea. The results found that by enabling access to temporal and biodiverse marine spaces such as rocky shores, place-based digital technologies can create new ways for communities to access and engage with the sea. Place-based digital technologies have the potential to create marine citizenship by building a connection between people and marine environments to care for the sea as a shared resource. We propose this can help establish a sense of place and contribute to marine stewardship in coastal communities.